2021
DOI: 10.1177/1049732321997133
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives on Family Mealtimes Related to Gastrostomy Tube Feeding in Children

Abstract: Built on the important functions daily routines serve families and child health, this study aimed to explore parents’ descriptions of mealtimes and food-related challenges when living with a child using a gastrostomy feeding tube. The study was informed by ecocultural theory and based on in-depth interviews combined with stimulated recall. The interviews of 10 parents were inductively analyzed by means of qualitative content analysis. Four main categories comprised the parents’ descriptions: “One situation, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The family in this study experienced a sense of relief when the G-tube was finally inserted, since it resulted in less pressure at mealtimes, which is in line with earlier research (Backman et al, 2021 ; Mårtensson et al, 2021 ). It has previously been confirmed that a G-tube insertion can result in an alteration in the family’s daily life (Russell et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The family in this study experienced a sense of relief when the G-tube was finally inserted, since it resulted in less pressure at mealtimes, which is in line with earlier research (Backman et al, 2021 ; Mårtensson et al, 2021 ). It has previously been confirmed that a G-tube insertion can result in an alteration in the family’s daily life (Russell et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…All these aspects contributed to a relaxed mealtime for the family. In order to reach optimal mealtimes after a G-tube insertion, commitment from a paediatric care team has been emphasized (Backman et al, 2021 ; Backman & Karlsson, 2021 ; Russell et al, 2018 ). Nevertheless, the G-tube also required the family to change, giving rise to new mealtime habits.…”
Section: Discussionmentioning
confidence: 99%
“…It affects not only the meals themselves, but also many other parts of family life. It is important that healthcare professionals ask about eating and eating difficulties as they are not always self-reported [96]. Nutritional management practices vary internationally and there is an urgent need for larger, coordinated, prospective intervention studies of nutrition in NMDs [97,98].…”
Section: Discussionmentioning
confidence: 99%
“…Non-physical causes—the practicalities of feeding of a vulnerable child with multiple medical issues in a busy family environment when, for many potential reasons, feeding is not necessarily a pleasurable experience 18–21. This includes parental/professional views towards type and method of feeding, altered perception of pain and discomfort, extreme sensitivity to certain textures and rigidity of feeding schedule associated with artificial feeding and lack of shared decision-making with families.…”
Section: Factors That Impact On Feed Tolerancementioning
confidence: 99%
“…Management of method and type of feed in children is a very emotive topic and therefore requires shared decision-making with the carers 8. Even with high workload associated with feeding, most parents are not willing to reduce their participation in feeding and decisions around feeding and have its root in parental identity and role in providing for the family 8 19. In children with nutritional deficiencies, enteral tube feeding support should be discussed and feeding plan individualised to meet the family’s needs.…”
Section: Getting the Balance Rightmentioning
confidence: 99%